The Relationship Between Self-Regulated Learning and Metacognition in Students Receiving Academic Achievement Scholarships - Rahayuningtyas, Nadya Saraswati; Murti, Heru Astikasari Setya (Psyche 165 Journal, 2025)
The Grade Point Average (GPA) is one part of the results of student learning achievement. For scholarship recipients with certain minimum requirements on GPA. Maintaining a GPA is certainly not easy for students and often encounter many challenges, especially in self-regulated learning and metacognition. The purpose of this study was to determine the relationship between self-regulated learning and metacognition in students receiving academic achievement scholarships. The research method used in this study was quantitative with a correlational research type. Participants in this study were 123 students receiving academic achievement scholarships at Satya Wacana Christian University Salatiga, participants were selected using a purposive sampling technique . The data analysis method used for the correlation test in this study used Spearman's Rho . The results of this study showed a positive relationship between self-regulated learning and metacognition with a Spearman's Rho correlation coefficient value of 0.634 and a significance of 0.000. This indicates that the higher the self-regulated learning ability of an individual, the higher the metacognition of the individual. This research has significant implications, particularly for students receiving academic achievement scholarships, for improving their metacognition by enhancing self-regulated learning . This suggests that students receiving academic achievement scholarships need to focus on self-regulation in learning, evaluate their learning process, and maintain self-motivation. The effective contribution of self-regulated learning to metacognition in students receiving academic achievement scholarships is 40.2%.